Ocimum gratissimum Linn. Leaves reduce the key enzymes activities relevant to erectile dysfunction in isolated penile and testicular tissues of rats - Oluwafemi Adeleke Ojo; Adebola Busola Ojo; Babatunji Emmanuel Oyinloye; Basiru Olaitan Ajiboye; Omosola Olufisayo Anifowose; Ayodeji Akawa; Oluranti Esther Olaiya; Oluwaseun Ruth Olasehinde; Abidemi Paul Kappo (BMC, 2019)
Abstract Background Ocimum gratissimum L. is a medicinal plant widely grown in tropical and subtropical regions with the leaf decoction usually taken in folk medicine to enhance erectile performance in men although the probable mechanism of actions remains undetermined. This study examined the inhibitory potentials of Ocimum gratissimum leaves on some key enzymes associated with erectile dysfunction in penile and testicular tissues of the rat. Methods Inhibitory effect of aqueous extract (1:10 w/v) of O. gratissimum leaves on the activities of phosphodiesterase-5 (PDE-5), arginase, angiotensin I -converting enzyme (ACE), and acetylcholinesterase (AChE) in penile and testicular tissues were assessed. Also, the extract was investigated for ferric reducing antioxidant property(FRAP) and 1,1-diphenyl-2-picryl-hydrazil (DPPH) radical scavenging abilities. Results The extract showed higher PDE-5 (IC50 = 43.19 μg/mL), ACE (IC50 = 44.23 μg/mL), AChE (IC50 = 55.51 μg/mL) and arginase (IC50 = 46.12 μg/mL) inhibitory activity in the penile tissue than PDE-5 (IC50 = 44.67 μg/mL), ACE (IC50 = 53.99 μg/mL), AChE (IC50 = 60.03 μg/mL) and arginase (IC50 = 49.12 μg/mL) inhibitory activity in the testicular tissue homogenate. Furthermore, the extract scavenged free radicals and in a dose-dependent manner. Conclusion The enzyme activities displayed might be associated with the bioactive compounds present in the extract which could possibly explain its use in the management of erectile dysfunction (ED).